Two-year prevalence rates of mental health and substance use disorder diagnoses among repeat arrestees - Lauren A. Magee; J. Dennis Fortenberry; Marc Rosenman; Matthew C. Aalsma; Sami Gharbi; Sarah E. Wiehe (BMC, 2021)
Abstract Background Individuals with mental illness and co-occurring substance use disorders often rapidly cycle through the justice system with multiple arrests. Therefore, is it imperative to examine the prevalence of mental health and substance use diagnoses among arrestees and repeat arrestees to identify opportunities for intervention. Methods We linked police arrest and clinical care data at the individual level to conduct a retrospective cohort study of all individuals arrested in 2016 in Indianapolis, Indiana. We classified arrestees into three levels: 1 arrest, 2 arrests, or 3 or more arrests. We included data on clinical diagnoses between January 1, 2014 and December 31, 2015 and classified mental health diagnoses and substance use disorder (SUD) based on DSM categories using ICD9/10 diagnoses codes. Results Of those arrested in 2016, 18,236 (79.5%) were arrested once, 3167 (13.8%) were arrested twice, and 1536 (6.7%) were arrested three or more times. In the 2 years before the arrest, nearly one-third (31.3%) of arrestees had a mental health diagnosis, and over a quarter (27.7%) of arrestees had an SUD diagnosis. Most of those with a mental health or SUD diagnosis had both (22.5% of all arrestees). Arrestees with multiple mental health (OR 2.68, 95% CI 2.23, 3.23), SUD diagnoses (OR 1.59, 95% CI 1.38, 1,82), or co-occurring conditions (1.72, 95% CI 1.48, 2.01) in the preceding 2 years had higher odds of repeat arrest. Conclusions Our findings show that linked clinical and criminal justice data systems identify individuals at risk of repeat arrest and inform opportunities for interventions aimed at low-level offenders with behavioral health needs.